Triplet Excited Carbonyls and Singlet Oxygen Formation During Oxidative Radical Reaction in Skin - Prasad, Ankush; Balukova, Anastasiia; Pospíšil, Pavel (Frontiers in Physiology, 2018)
The skin is the largest organ in the body and is consistently exposed to aggressive environmental attack (biological/physical/chemical etc.). Reactive oxygen species (ROS) are formed during the normal oxidative metabolism which enhances to a lethal level under stress condition referred to as oxidative stress. While, under normal conditions, cells are capable of dealing with ROS using non-enzymatic and enzymatic defense system, it can lead to a critical damage to cell system via the oxidation of cellular components under stress condition. Lipid peroxidation is a well-established mechanism of cellular injury in all kinds of organisms and it is often used as an indicator of oxidative stress in cells and tissues. In the presence of metal ions, ROS such as hydrogen peroxide (H2O2) produces highly reactive hydroxyl radical (HO•) via Fenton's reaction. In the current study, we have used the porcine skin (intact pig ear/skin biopsies) as an ex-vivo/in-vitro model system to represent human skin. Experimental results have been presented on the participation of HO• in the initiation of lipid peroxidation and thereby leading to the formation of reactive intermediates and the formation of electronically excited species eventually leading to ultra-weak photon emission. To understand the participation of different electronically excited species in the overall ultra-weak photon emission, the effect of a scavenger of singlet oxygen (1O2) on photon emission in the visible and near-infrared region of the spectrum was measured which showed its contribution. In addition, measurement with interference filter with a transmission in the range of 340 540 nm reflected a substantial contribution of triplet carbonyls (3L=O*) in the photon emission. Thus, it is concluded that during the oxidative radical reactions, the ultra-weak photon emission is contributed by the formation of both 3L=O* and 1O2. The method used in the current study is claimed to be a potential tool for non-invasive determination of the physiological and pathological state of human skin/dermatological research.